Critical Points Concerning Artisanal Fishing: an Analysis from the Perspective of Artisanal Fishers in Southeastern Brazil - Abreu, Juliana Silva; Côrtes, Laura Helena de Oliveira; Zappes, Camilah Antunes (Sociedade & Natureza, 2024)
In Southeastern Brazil, artisanal fishing communities reside, operate and suffer from interference originating from various economic branches. Thus, this study is aimed at identifying the critical points concerning the practice of artisanal fishing from the traditional knowledge of artisanal fishers in the coastal mesoregion of ES. 102 ethnographic interviews were conducted in 2022 with artisanal fishers through a semistructured questionnaire containing both open and closed questions. The critical points of fishing were identified through a SWOT analysis (strengths, weaknesses, opportunities, and threats). All the participants were men (n=102; 100%), and they reported that negative critical points (weaknesses and threats) exert the greatest influence on fishing. From the perspective of these fishers, the main problems that interfere with artisanal fishing are the lack of adequate fish storage, the precariousness of the vessels, the reduction in fish stocks, the high perishability of fish, the devaluation of traditional knowledge, and the presence of middlemen that prevent the commercialization of fish production from moving directly from the fisher to the final consumer. The identification of these critical points enables the recognition of flaws in the production chain and the realization that they can be minimized through public policies and comanagement strategies related to the economic, ecological, and social development of the sector.